Elevated Soluble VEGF Receptor sFlt-1 Correlates with Endothelial Injury in IgA Nephropathy - Zhai, Ya-Ling (Public Library of Science, 2014)
BACKGROUND: Endothelial injury, which may present clinically as hypertension, proteinuria and increased von Willebrand Factor (vWF) level, is a common manifestation in IgA nephropathy (IgAN). However, causal factors for endothelial injury in IgAN are not completely understood. An imbalance of vascular endothelial growth factor/Soluble fms-like tyrosine kinase-1 (VEGF/sFlt-1) has been observed in many diseases with endothelial dysfunction, including pre-eclampsia and diabetic retinopathy, but whether it contributes to endothelial injury in IgAN requires further exploration. METHODS: Initially, 96 IgAN patients and 22 healthy volunteers were enrolled as a discovery cohort. VEGF/sFlt-1, sFlt-1 and VEGF levels were compared between patients with IgAN and healthy volunteers to explore the underlying factors that contribute to endothelial injury in IgAN. The identified contributor (sFlt-1) was further confirmed in a replication cohort, which included 109 IgAN patients and 30 healthy volunteers. Correlations of sFlt-1 with hypertension, proteinuria, Oxford-E score and plasma vWF were further evaluated in the combined 205 patients with IgAN. RESULTS: VEGF/sFlt-1 levels were significantly lower in IgAN patients than healthy volunteers (0.33±0.27 vs. 0.43±0.22, p = 0.02) in the discovery cohort. Within the ratio, plasma sFlt-1 levels were significantly elevated (101.18±25.19 vs. 79.73±18.85 pg/ml, p<0.001), but plasma VEGF levels showed no significant differences. Elevated sFlt-1 levels in the replication cohort were confirmed in IgAN patients (93.40±39.78 vs. 71.92±15.78 pg/ml, p<0.001). Plasma sFlt-1 levels in IgAN patients correlated with proteinuria (severe (>3.5 g/d) vs. moderate (1–3.5 g/d) vs. mild (<1 g/d) proteinuria: 115.95±39.09 vs. 99.89±28.55 vs. 83.24±33.92 pg/ml; severe vs. mild: p<0.001, moderate vs. mild p = 0.001, severe vs. moderate: p = 0.014), hypertension (with vs. without hypertension: 107.87±31.94 vs. 87.32±32.76 pg/ml, p = 0.015) and vWF levels (r = 0.161, p = 0.021). CONCLUSIONS: The present study found elevated sFlt-1 in IgAN patients and further identified its correlation with proteinuria, hypertension and vWF levels. These results suggested that elevated sFlt-1 contributes to endothelial injury in IgAN.